Acute toxicological studies of the main organosulfur compound derived from Allium sp. intended to be used in active food packaging. (August 2015) - Llana-Ruiz-Cabello, María; Gutiérrez-Praena, Daniel; Puerto, María; Pichardo, Silvia; Moreno, F. Javier; Baños, Alberto; Nuñez, Cristina; Guillamón, Enrique; Cameán, Ana María
Highlights: PTSO exhibits interesting antimicrobial and antioxidant properties for food industry. High concentrations of PTSO cause cytotoxic and morphological damages in human cells. PTSO is a promising active substance for active food packaging at low concentrations. Abstract: Some plant extracts have been proposed as potential alternative to the use of synthetic preservatives in the food industry. Among those, extracts from Allium species exhibit interesting antimicrobial and antioxidant properties for the food packaging industry. The present work aims to assess the usefulness and potential safety of the major organosulfur compound present in a commercial Allium sp. extract (PROALLIUM AP®), namely propyl thiosulfinate oxide (PTSO). For this purpose, its antimicrobial activity was studied in a wide range of microorganisms. Moreover, cytotoxicity and ultrastructural cellular damages caused by PTSO were studied in two human cell lines, Caco-2 and HepG2, being the colonic cells more sensitive to this compound. Finally, the protective role of PTSO against an induced oxidative situation was evaluated in the human intestinal Caco-2 cells. The results revealed damage at high concentration, although no significant adverse effects were recorded for the concentration to be used in food packaging. Moreover, the in vivo study also revealed the potential safety use at the established concentrations. In addition, the antimicrobial properties and the antioxidant role of PTSO were confirmed. Therefore, this compound could be considered as a good natural alternative to synthetic preservatives used in the food packaging industry.